Wear Testing of Aluminum AA1060 according to ASTM G65 Standard - Estrada Yanes, Reniel; Negrín Hernández, Luis Iván (My University, 2017)
Actually, the study of the tribological behavior of materials of machine elements is necessary because the industry has increased the interest in making tribological systems more efficient. Wear is found in most of the production processes and can occur through various mechanisms, such as adhesion, abrasion, erosion, fatigue and impact. One of the main mechanisms is abrasive wear, which occurs frequently and appears when high hardness particles make contact with the ductile surface of machine elements, resulting in deformation and subsequent cutting and lifting the surface material. In this work, the wear testing is carried out according to the ASTM G65 standard to determine the wear coefficient (K) of four aluminum AA1060 specimens. In addition, wear measurements are made when the rubber wheel performs 2000, 4000 and 6000 revolutions to calculate the wear rate (Q) of the material.
Keywords: Wear Coefficient; Wear Rate; Aluminum AA1060; Abrasive Wear; ASTM G65